Jelly fish, Acromitus flagellates as a Potential Source of Hyaluronic Acid for Cosmetic Applications: Jelly fish as a Potential Source of Hyaluronic Acid - Raj, Rehana; Sreelakshmi, K. R.; Minimol, V. A.; Ninan, George; Asha, K. K. (Fishery Technology, 2025)
Hyaluronic acid (HA) is a valuable bioactive polysaccharide that has numerous applications in the nutricosmetic and cosmetic industries. The tremendous increase of jelly fish in fishing environments has led to a huge global demand for better ways to utilize the organism. The present study investigated the potential for extracting hyaluronic acid from the jelly fish, Acromitus flagellates. The extracted powder was fine, hygroscopic and off-white in colour. The viscosity was measured at different concentrations of 1 mg/ml to 5 mg/ml and at the highest shear rate studied (450 s-1), the maximum viscosity obtained was 1.85cp. Fourier Transform Infrared Spectroscopy (FTIR) confirmed the structure of hyaluronic acid with the presence of disaccharide repeats of D-glucuronic acid (GlcUA) and N-acetylglucosamine (GlcNAc) adjoined alternatively by β-1,3 and β-1,4 glycosidic bonds. The UV-Visible spectroscopic absorption data of the extracted sample showed similar characteristics when compared to the standard. Protein contamination was not observed in the SDS PAGE analysis. The moisture retention ability of the extracted hyaluronic acid, as estimated by in vitro analysis, was better than glycerol up to 4h. Hence, Acromitus flagellates is an ideal candidate for extraction of hyaluronic acid that can be applied in cosmetic and pharmaceutical formulations.